A FORMAL PROOF OF THE KEPLER CONJECTURE. (29th May 2017) - HALES, THOMAS; ADAMS, MARK; BAUER, GERTRUD; DANG, TAT DAT; HARRISON, JOHN; HOANG, LE TRUONG; KALISZYK, CEZARY; MAGRON, VICTOR; MCLAUGHLIN, SEAN; NGUYEN, TAT THANG; NGUYEN, QUANG TRUONG; NIPKOW, TOBIAS; et al.
Abstract : This article describes a formal proof of the Kepler conjecture on dense sphere packings in a combination of the HOL Light and Isabelle proof assistants. This paper constitutes the official published account of the now completed Flyspeck project.